Fire blight : the disease and its causative agent, Erwinia amylovora (CABI, 2000)
This book is the first multi-authored book on fire blight, the most devastating bacterial disease of apples and pears. It is divided into three sections. The first section is about the disease: its epidemiology, its worldwide distribution and its economic importance, the host range of the pathogen and how it migrates and survives in the fruit tissues. The second section is about the causal agent, Erwinia amylovora: its general characteristics as a member of the Enterobacteriaceae, but also the weapons it uses to cause disease: amylovoran, harpin, avirulence factors and siderophores. In the third section, the authors address the difficult problems of fire blight control. They look at chemical control, problems associated with streptomycin resistance, potential and limitations of traditional breeding and transgenic plants, and risk assessment strategies for the control of fire blight in orchards and in nurseries.